Inflation and Economic Growth Nexus in Egypt - Bey, Mousaab (2012)
The moderate and stable inflation rates are promoting important factors in the development process of a country, and hence economic growth. Moderate inflation supplements return to savers, enhances investment. and therefore, accelerates economic growth of the country. This paper empirically explores the present relationship between inflation and economic growth in the context of Egypt. Using annual data set on real GDP and CPI for the period of 1980 to 2010, an assessment of empirical evidence is acquired through the co-integration and error correction models. Further, it explores a policy issue of what is the threshold level of inflation for the economy using the threshold autoregressive models. The empirical evidence demonstrates that there exists a long-run and a short-run relationship between inflation and economic growth. In addition, the estimated threshold model suggests 15 percent as the threshold level (i.e., structural break point) of inflation above which inflation adversely affects economic growth.